Incidence of cardiovascular events in patients with atrial fibrillation anticoagulated with rivaroxaban after 2.5 years of follow-up: not all is stroke or bleeding. (14th October 2021) - Anguita Sanchez, M; Ruiz Ortiz, M; Marin, F; Sanmartin, M; Rafols, C; Masjuan, J; Urena, I; Baron Esquivias, G; Lekuona, I; Perez Cabeza, A; Vazquez Rodriguez, J.M; ,
Abstract: Introduction: Atrial fibrillation (AF) is not a benign arrhythmia, but is associated with an increase in mortality, above all related to the risk of suffering thromboembolic events, mainly stroke. The use of oral anticoagulants (OAC) reduces this risk, but increases the risk of serious bleeding. The DOACs have been shown to be superior to the classic vitamin K antagonists (VKAs). It is not as well known whether AF is associated with an increase in other serious cardiac events. Purpose: The objective of this analysis was to assess the incidence of stroke, major bleeding, total mortality and major adverse cardiac events [MACE, defined as cardiac mortality (including death for coronary events, progressive heart failure death and sudden cardiac death), coronary revascularization, myocardial infarction] in a contemporary series of patients with AF anticoagulated with rivaroxaban. Methods: To do this, we have analyzed a series of 1, 433 patients with AF, anticoagulated with rivaroxaban for at least the previous 6 months, consecutively included in the first half of year 2017 in 79 Spanish centers (EMIR study), and followed for 2.5 years. Results: Mean age was 74.2±9.7 years, 44.5% being women. Prevalence of diabetes was 27.1%, chronic renal failure 16.1%, coronary heart disease 16.4% and heart failure 22.7%. 2MACE score was 1.8±1.4, CHA2DS2-VASc was 3.5±1.5 and HAS-BLED 1.6±1.0. 77.1% of patients received 20 mg/ day of rivaroxaban and 22.9% 15 mg/day. After a follow-up of 2.5 years, the annual rate (events/100 patients/year) of myocardial infarction was 0.16 (all non-STEMI), coronary revascularization 0.28, cardiac death 0.63 (sudden 0.16, heart failure 0.41, other 0.06), overall MACE 1.07 and overall mortality 2.73, while the incidence of stroke was 0.57 / 100 patients / year (ischemic 0.35, haemorrhagic 0.22) and major bleeding 1.04 (gastrointestinal 0.63, intracranial 0.28). Conclusion: In a current series of patients with AF anticoagulated with rivaroxaban, the incidence of embolic and hemorrhagic complications and mortality are low, while the incidence of serious cardiac events is significant, being overall similar to that of stroke and major bleeding. Attention must be paid to the prevention and diagnosis of these problems. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Bayer Hispania